In Vitro Antimicrobial and Anticancer Peculiarities of Ytterbium and Cerium Co-Doped Zinc Oxide Nanoparticles - Essia Hannachi; Firdos Alam Khan; Yassine Slimani; Suriya Rehman; Zayneb Trabelsi; Sultan Akhtar; Ebtesam A. Al-Suhaimi (Biology, 2022)
Zinc oxide nanoparticles (ZnO NPs) are a promising platform for their use in biomedical research, especially given their anticancer and antimicrobial activities. This work presents the synthesis of ZnO NPs doped with different amounts of rare-earth ions of ytterbium (Yb) and cerium (Ce) and the assessment of their anticancer and antimicrobial activities. The structural investigations indicated a hexagonal wurtzite structure for all prepared NPs. The particle size was reduced by raising the amount of Ce and Yb in ZnO. The anticancer capabilities of the samples were examined by the cell viability MTT assay. Post 48-h treatment showed a reduction in the cancer cell viability, which was x = 0.00 (68%), x = 0.01 (58.70%), x = 0.03 (80.94%) and x = 0.05 (64.91%), respectively. We found that samples doped with x = 0.01 and x = 0.05 of Yb and Ce showed a better inhibitory effect on HCT-116 cancer cells than unadded ZnO (x = 0.00). The IC50 for HCT-116 cells of Ce and Yb co-doped ZnO nanoparticles was calculated and the IC50 values were x = 0.01 (3.50 µg/mL), x = 0.05 (8.25 µg/mL), x = 0.00 (11.75 µg/mL), and x = 0.03 (21.50 µg/mL). The treatment-doped ZnO NPs caused apoptotic cell death in the HCT-116 cells. The nanoparticles showed inhibitory action on both C. albicans and E. coli. It can be concluded that doping ZnO NPs with Yb and Ce improves their apoptotic effects on cancer and microbial cells.